Pregnancy and COVID-19: incidence of childbirth complications (Research, Society and Development, 2023)
Introduction: COVID-19 manifests itself as a highly contagious lung disease and its severity can range from no symptoms to critical illness. With regard to the effect of SARS-CoV-2 infection during pregnancy, data are still relatively limited and heterogeneous. Objective: the present study seeks to evaluate the incidence of gestational complications in women with SARS-CoV-2 infection in the city of Itajubá - Minas Gerais, in a university hospital. Methodology: this is a cross-sectional and documentary study, carried out at the Hospital das Clínicas de Itajubá, where data collection was carried out through the review of medical records of parturients positive for COVID-19 admitted to the hospital service mentioned above, in the period of March from 2020 to September 2021. Results: 40 pregnant patients who met the selection criteria were identified. From the outcome of these deliveries, it was found that 35 deliveries were cesarean sections, 2 normal deliveries and 3 were not informed in the medical records. The indications described for cesarean delivery were: maternal instability with respiratory failure, pre-eclampsia, premature rupture of ovular membranes, placental abruption, fetal distress. No maternal deaths were reported. Conclusion: the gestational complications most reported in the literature and existing in the findings of this research were: respiratory failure, preeclampsia, premature birth, premature rupture of the membrane, placental abruption and fetal distress. There is also a high cesarean rate.